Childhood Intra-Thoracic Tuberculosis Clinical Presentation Determines Yield of Laboratory Diagnostic Assays - Urvashi B. Singh; Yogita Verma; Rakhi Jain; Aparna Mukherjee; Hitender Gautam; Rakesh Lodha; Sushil K. Kabra (Frontiers Media S.A., 2021)
Diagnosis of intra-thoracic tuberculosis (ITTB) in children is difficult due to the paucibacillary nature of the disease, the challenge in collecting appropriate specimens, and the low sensitivity of smear microscopy and culture. Culture and Xpert MTB/RIF provide higher diagnostic yield in presumptive TB in adults than in children. Current study was designed to understand poor yield of diagnostic assays in children. Children with presumptive ITTB were subjected to gastric aspirates and induced sputum twice. Samples were tested by Ziehl-Neelsen stain, Xpert MTB/RIF-assay, and MGIT-960 culture. Subjects were grouped as Confirmed, Unconfirmed, and Unlikely TB, and classified as progressive primary disease (PPD, lung parenchymal lesion), and primary pulmonary complex (PPC, hilar lymphadenopathy) on chest X-ray. Of children with culture-positive TB 51/394 (12.9%), culture-negative TB 305 (77.4%), and unlikely TB 38 (9.6%), 9 (2.3%) were smear positive, while 95 (24.1%) were Xpert-MTB/RIF positive. Xpert-MTB/RIF detected 40/51 culture confirmed cases (sensitivity 78.4% and NPV 96.3%). Culture was positive in more children presenting as PPD (p < 0.04). In culture-negative TB group, Xpert positivity was seen in 31% of those with PPD and 11.9% in those with PPC (p < 0.001).Conclusion: Xpert-MTB/RIF improved diagnosis by 2-fold and increased detection of MDR-TB. Both liquid culture and Xpert-MTB/RIF gave higher yield in children with lung parenchymal lesions. Children with hilar lymphadenopathy without active lung parenchymal lesions had poor diagnostic yield even with sensitive nucleic acid amplification tests, due to paucibacillary/localized disease, suggesting possible utility of invasively collected samples in early diagnosis and treatment.